2014
DOI: 10.3329/jbsa.v24i2.19804
|View full text |Cite
|
Sign up to set email alerts
|

Wound infection in surgery department in BSMMU: A study of 100 cases

Abstract: Background Surgical site infections (SSI) are the most common nosocomial infection in surgical patients, accounting for 38% of all such infections, and are a significant source of postoperative morbidity resulting in increased hospital length of stay and increased cost. Objectives To find out the incidence of wound infection in patients following elective surgery and the most likely causative organisms and their resistance pattern. Methods Prospective data were collected on 496 surgical patients admitted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…This is higher than that of Sickder et al (14.13%) but lower than that of Mawalla et al (26%) but very similar to the study done by Nur-e-elahi and colleagues in BSMMU (20.16%). [14][15][16][17][18] In our study 73% SSIs were superficial infections and 27% were deep. In comparison of another study, done by Sickder and colleagues, 58.1% SSIs were superficial and 41.9% were deep.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This is higher than that of Sickder et al (14.13%) but lower than that of Mawalla et al (26%) but very similar to the study done by Nur-e-elahi and colleagues in BSMMU (20.16%). [14][15][16][17][18] In our study 73% SSIs were superficial infections and 27% were deep. In comparison of another study, done by Sickder and colleagues, 58.1% SSIs were superficial and 41.9% were deep.…”
Section: Discussionmentioning
confidence: 85%
“…This corresponded with the findings of Nur-e-elahi et al in BSMMU. 16 In their study highest number of infections were noted in fifth decade of life.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…15,16,17 Nur-e-Elahi M et al found 20.16% SSI incidence rate in surgery department of BSMMU, which is almost similar to this study. 18 In 2018, a comparative study in two tertiary care hospitals in Dhaka reported rates of only 3.0-8.92%. 19 Another study conducted in both general surgery and orthopedic ward in a tertiary care center in Barisal found overall prevalence rate of 14.3%.…”
Section: Discussionmentioning
confidence: 99%
“…There is no conclusive reported information available in Bangladesh as to the percentage of SSI incidents each year and the types of surgical wound involved in every case. However, generally, there are information of such infections that predisposes heavy burden of morbidity with subsequent financial expenses 6 . The present study carried out a research on the presence and comparative prevalence of a few important virulence genes and drug resistance patterns of Staphylococcus aureus isolates from surgical site infections and tried to correlate these two results.…”
Section: Introductionmentioning
confidence: 99%